Implant Charge Differences Between Distal Radius Fixation Constructs (CPT 25607, 25608, and 25609). (September 2022) - Goodman, Avi D.; Modest, Jacob M.; Johnson, Joey P.; Hayda, Roman A.; Got, Christopher J.; Gil, Joseph A.; Weiss, Arnold-Peter C.
Background: Implants are a significant contributor to health care costs. We hypothesized that extra-articular fracture patterns would have a lower implant charge than intra-articular fractures and aimed to determine risk factors for increased cost. Methods: In total, 163 patients undergoing outpatient distal radius fracture fixation at 2 hospitals were retrospectively reviewed stratified by Current Procedural Terminology codes. Implants and associated charges were noted, as were sex, age, insurance status, surgeon specialty, and location. Bivariate and multivariable regression were used to determine associations. Results: Total implant charges were significantly lower for 25607 (extraarticular, 3, 348) than 25608 (2-part intraarticular, 3, 859) and 25609 (3+ part intraarticular, 3, 991). In addition, intra-articular fractures had higher charges for distal screws/pegs and bone graft. Charge was lower when surgery was performed at a trauma center. There was no charge difference associated with insurance status, age, sex, hand surgery specialty, or fellow status. Substantial intersurgeon variation existed in all fracture types. Conclusion: Distal radius fractures may represent a good model for examining implant costs. Extra-articular fractures had lower implant charges than intra-articular fractures. These data may be used to help construct pricing for distal radius fracture bundles and potential cost savings.